2022
DOI: 10.3390/cells11162484
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Roles of Ethylene Response Factors in Pathogen Response and Ripening in Fleshy Fruit

Abstract: Fleshy fruits are generally hard and unpalatable when unripe; however, as they mature, their quality is transformed by the complex and dynamic genetic and biochemical process of ripening, which affects all cell compartments. Ripening fruits are enriched with nutrients such as acids, sugars, vitamins, attractive volatiles and pigments and develop a pleasant taste and texture and become attractive to eat. Ripening also increases sensitivity to pathogens, and this presents a crucial problem for fruit postharvest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 134 publications
(174 reference statements)
0
11
0
Order By: Relevance
“…D6 , and SlERF . D7 expression is induced in response to B. cinerea infection of red ripe tomato fruits but not wounding [81], suggesting a role in the defense response specific to pathogen detection. None of these TFs have been implicated in EBDC defense before, and we report a role in biotic stress in tomato for SlbZIP07, NFXL1, SlERF .…”
Section: Resultsmentioning
confidence: 99%
“…D6 , and SlERF . D7 expression is induced in response to B. cinerea infection of red ripe tomato fruits but not wounding [81], suggesting a role in the defense response specific to pathogen detection. None of these TFs have been implicated in EBDC defense before, and we report a role in biotic stress in tomato for SlbZIP07, NFXL1, SlERF .…”
Section: Resultsmentioning
confidence: 99%
“…Although a number of TF families such as ERF, WRKY, NAC, bHLH, and bZIP have been reported to be involved in plant response to pathogen attack (Campos et al ., 2022). Among these, ERFs are also recognized as critical transcription factors that regulate responses to fungi in various fresh fruits, including tomato (S. Li et al ., 2022), to date the role and action mode of ERFs in fruit defense against B. cinerea infection, one of the most devastating pathogens causing enormous postharvest fruit losses, remain largely unclear. Furthermore, phosphorylation of several TFs by MPKs has been also demonstrated in regulation of pathogen resistance, but it is still unknown about whether the MPK signaling pathway participates in postharvest disease resistance or functions directly upstream of ERFs in fruits (Sun & Zhang, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…All three TFs families are well characterised and their role concerning abiotic stress in plants was massively investigated while reports about abiotic stress particularly virus infection have been less abundant [ 83 , 84 ]. Interestingly, ERF is the highest TFs family identified in our study and is widely reported to be involved in responses to numerous biotic stresses in diverse plant species [ 85 ]. ERFs are part of the (AP2/ERFs) TF family and are one of the biggest plant TF families.…”
Section: Discussionmentioning
confidence: 99%
“…ERFs are part of the (AP2/ERFs) TF family and are one of the biggest plant TF families. ERFs regulate ethylene signalling and play roles in plant resistance to pathogens and fruit ripening [ 85 ]. Recently, ERF association with plant immune responses and resistance against plant viruses has been reported and its virus resistance mechanism is under investigation [ 86 , 87 ].…”
Section: Discussionmentioning
confidence: 99%